(untitled) (Research, Society and Development, 2022)
The study aimed to evaluate the level of knowledge of pharmacists about the Clinical Protocol and Therapeutic Guidelines (CPTG)/Dyslipidemia, before and after training, for the implementation of clinical services in a public pharmacy for dispensing specialized medicines and the perception of dyslipidemic users attended at this pharmacy, on the use, adverse reactions and health promotion measures, before and after the implementation of pharmaceutical care. This was a cross-sectional, observational, descriptive and qualitative study on the perception of patients regarding the use of medicines and health promotion measures, and cross-sectional, observational and descriptive in relation to the level of knowledge of pharmacists about the treatment and protocol of dyslipidemia, before and after training on CPTG/Dyslipidemia. After the implementation of pharmaceutical care, patients showed a significant change in their perception of the reason for and the need to use the medicines, the correct way to use these medicines, as well as the need to adopt a healthy diet and physical activity. After training pharmacists on CPTG/Dyslipidemia, there was an improvement in patient orientation, which can be seen by evaluating the perception of these patients about the importance of correct use of their medicines and lifestyle changes after training. In conclusion, it is understood that the training and updating of the pharmacist are important, as well as, it is necessary for this professional to act directly in the dispensing of medicines and patient guidance to promote the rational use of medicines and health promotion.